Cannabidiol exhibits anxiolytic but not antipsychotic property evaluated in the social interaction test - Almeida, Valéria de [UNIFESP] (2013)
Cannabidiol (CBD), a non-psychotomimetic compound of the Cannabis sativa, has been reported to have central therapeutic actions, such as antipsychotic and anxiolytic effects. We have recently reported that Spontaneously Hypertensive Rats (SHRs) present a deficit in social interaction that is ameliorated by atypical antipsychotics. in addition, SHRs present a hyperlocomotion that is reverted by typical and atypical antipsychotics, suggesting that this strain could be useful to study negative symptoms (modeled by a decrease in social interaction) and positive symptoms (modeled by hyperlocomotion) of schizophrenia as well as the effects of potential antipsychotics drugs. At the same time, an increase in social interaction in control animals similar to that induced by benzodiazepines is used to screen potential anxiolytic drugs. the aim of this study was to investigate the effects of CBD on social interaction presented by control animals (Wistar) and SHRs. the lowest dose of CBD (1 mg/kg) increased passive and total social interaction of Wistar rats. However, the hyperlocomotion and the deficit in social interaction displayed by SHRs were not altered by any dose of CBD. Our results do not support an antipsychotic property of cannabidiol on symptoms-like behaviors in SHRs but reinforce the anxiolytic profile of this compound in control rats. (C) 2012 Elsevier Inc. All rights reserved.